PREVALENCE OF EPISIOTOMY AND FACTORS ASSOCIATED WITH PRACTICE OF EPISIOTOMY AT SAINT PAUL’S HOSPITAL MILLENNIUM MEDICAL COLLEGE: A CROSS SECTIONAL STUDY - Tefera, Tobiaw; Kebede, Birhanu; Mekonen, Tadios (Ethiopian Journal of Reproductive Health, 2019)
ABSTRACT INTRODUCTION: Episiotomy is a surgical incision made on the perineum to widen the vaginal opening for delivery. Although rate of episiotomy decreased, it is still one of the most commonly performed procedures in obstetrics (1). OBJECTIVE: The objective of the study is to determine the prevalence of episiotomy and identify risk factors associated with the practice of episiotomy at (Saint Paul’s Hospital Millennium Medical College) SPHMMC. METHODOLOGY: Hospital-based cross-sectional study was conducted from February 1/2016 to July 1/2016. All mothers who gave birth vaginally were included in the study. Data was entered in to epi info version 7 and exported into SSPS statistical package version 16 and analyzed. Both bivariate and multivariate analysis were used to see the association of the dependent and independent variables with p-value <0.05 considered statistically significant. RESULT: A total of 405 participants were included in the study. The prevalence of episiotomy was 65.4%. Both Bivariate & Multivariate analysis showed that nulliparity, duration of second stage of labor more than 90-minute, instrumental delivery, assisted breech delivery & birth weigh more than 4,000 gm were strongly associated with episiotomy (p- value < 0.005). CONCLUSIONS AND RECOMMENDATIONS: The prevalence of episiotomy (65.4%) at SPHMMC is higher than the findings in other studies in Ethiopia & the WHO’s recommendation of 5- 10%. Nulliparity, duration of second stage of labour more than 90 minutes, instrumental & breech vaginal deliveries and birth weight of more than 4000 gm were independent risk factors for episiotomy. KEYWORDS: Episiotomy, prevalence, risk factors